Precision evaluation for different GNSS RINEX 3 using online services and open-source software PPP-MANS - Shehata, Ashraf G.; Zarzoura, Fawzi H.; El-Mewafi, Mahmoud (Geodesy and Cartography, 2023)
It is critical to evaluate the reliability of using free online processing software for Global Navigation Satellite System post-processing since the advancement of GNSS gives satellite navigation customers all over the world great benefits. AUSPOS, IBGE, Magic GNSS, CSRS-PPP, and open-source software are some of the online processing solutions being evaluated for accuracy in this study. GNSS observations from IGS were used to conduct field observations using RINEX 3 data from three stations, with an observation duration of 30 seconds. After data acquisition, it was processed with online and free software that made use of GPS, GPS, and GLONASS. When compared to coordinates obtained from reference stations, the relative differences and correctness of the coordinates generated by each piece of software were then evaluated. coordinates in the ITRF14 reference for the X, Y, and Z directions. Online GNSS processing services may be used with greater accuracy for engineering and geodetic applications and are simple to use without the need for GNSS data processing expertise.